1984
DOI: 10.1128/mcb.4.4.761
|View full text |Cite
|
Sign up to set email alerts
|

Superkiller mutations in Saccharomyces cerevisiae suppress exclusion of M2 double-stranded RNA by L-A-HN and confer cold sensitivity in the presence of M and L-A-HN.

Abstract: In an mktl host, L-A-HN double-stranded RNA excludes M2 double-stranded RNA at 30°C but not at 20°C. Recessive mutations suppressing the exclusion of M2 by L-A-HN in an mktl host include six ski (superkiller) genes, three of which (ski6, ski7 and ski8) are new genes. The dominant mutations in one gene (MKS50) and recessive mutations in at least two genes (mksl and mks2) suppress M2 exclusion by L-A-HN but do not show other characteristics of ski mutations and thus define a new class of killer-related chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
158
0
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(165 citation statements)
references
References 34 publications
5
158
0
2
Order By: Relevance
“…hSki8 is also a component of the human SKI (hSKI) complex. The yeast SKI complex and Exosome are both genetically required for 3Ј-to-5Ј mRNA decay (Ridley et al 1984;Masison et al 1995;Anderson and Parker 1998;Brown et al 2000;Araki et al 2001;Mitchell and Tollervey 2003). We found that hSKI localizes to transcriptionally active genes in an hPAF-dependent manner.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…hSki8 is also a component of the human SKI (hSKI) complex. The yeast SKI complex and Exosome are both genetically required for 3Ј-to-5Ј mRNA decay (Ridley et al 1984;Masison et al 1995;Anderson and Parker 1998;Brown et al 2000;Araki et al 2001;Mitchell and Tollervey 2003). We found that hSKI localizes to transcriptionally active genes in an hPAF-dependent manner.…”
mentioning
confidence: 70%
“…Yeast Ski2, Ski3, and Ski8, all subunits of the SKI complex, are essential for 3Ј-to-5Ј mRNA decay (Ridley et al 1984;Masison et al 1995). Additionally, the ySKI complex interacts with the Exosome, a multi-subunit complex essential for 3Ј-5Ј mRNA decay (Anderson and Parker 1998;Araki et al 2001;Mitchell and Tollervey 2003).…”
Section: Hski Complex Localizes To Both Cytoplasm and Nucleusmentioning
confidence: 99%
See 1 more Smart Citation
“…The maklO(Ts) marker was tested by temperature-sensitive maintenance of [HOK] activity, a marker located on L-A dsRNA. The ski2-2 marker was determined by suppression of [NEX] activity in a diploid resulting from a cross with a ski2-2 mktl strain which has M2 and L-A-HN dsRNAs (16). ski2-21ski2-2 mktllmktl homozygous diploids will maintain M2 stably at 30°C in the presence of L-A-HN, while ski2-21+ mktllmktl diploids will lose M2 under these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The superkiller (SKI ) genes in yeast are encoded in the nuclear genome+ They were initially identified from mutations that caused overexpression of a killer toxin encoded by the endogenous double-stranded RNA, denoted as M, a satellite of the double-stranded RNA virus L-A (Toh-e et al+, 1978;Ridley et al+, 1984;reviewed in Wickner, 1996areviewed in Wickner, , 1996b)+ Subsequent work demonstrated that SKI2, SKI3, SKI6, SKI7, and SKI8 are necessary to repress translation of poly(A) minus RNAs (Widner & Wickner, 1993;Masison et al+, 1995;Benard et al+, 1998Benard et al+, , 1999, whereas SKI1 is XRN1 (Johnson & Kolodner, 1995) and encodes a 59-exoribonuclease (Larimer et al+, 1992)+ In strains lacking both M and L-A, double mutants of xrn1⌬ and either ski2 or ski3 mutations are not viable (Johnson & Kolodner, 1995) or are temperature sensitive (Benard et al+, 1999), depending on strain background+ These observations indicate that the SKI genes are necessary for a general cellular function in addition to an antiviral activity (Johnson & Kolodner, 1995)+ ski8 mutations also are synthetic lethal with xrn1⌬ (Jacobs Anderson & Parker, 1998; J+T+ Brown & A+W+ Johnson, unpubl+ observation)+ More recently, SKI2, SKI3, SKI6, and SKI8 have been shown to be required for a 39-mRNA degradation pathway (Jacobs Anderson & Parker, 1998)+ Ski6p/Rrp41p itself is a 39-exoribonuclease and is an essential component of the exosome (Mitchell et al+, 1997), a large complex of 39-exoribonucleases that is involved in multiple RNA processing events in ribosome biogenesis (Mitchell et al+, 1996(Mitchell et al+, , 1997Zanchin & Goldfarb, 1999)+…”
Section: Introductionmentioning
confidence: 99%